Metabolic and inflammatory status in prepuberty and early adulthood for individuals with a history of extrauterine growth restriction: a cohort study - Laura Palomino-Fernández; Inmaculada Velasco; Belén Pastor-Villaescusa; Katherine Flores-Rojas; María de la Cruz Rico; Juan Roa; Ángel Gil; Mercedes Gil-Campos (Journal of Translational Medicine, 2025)
Abstract Background Perinatal growth and nutrition have been shown to be determinants in the programming of different tissues, such as adipose tissue, predisposing individuals to metabolic alterations later in life. Previous studies have documented an increased risk of metabolic disturbances and low-grade inflammation in prepubertal children with a history of extrauterine growth restriction (EUGR). The aim of this study was to evaluate possible alterations resulting from impaired growth during early childhood and their impact on young adult health. Methods This is a longitudinal, descriptive and analytical study of a cohort with a history of EUGR recruited at prepubertal age and followed up for 10 years until the end of puberty. Anthropometric measurements, blood pressure, biochemical parameters related to lipid and carbohydrate metabolism and plasma adipokines and cytokines were analyzed. Results Compared with prepubertal children, young adults EUGR presented increased abdominal circumference percentiles. Moreover, insulin levels and the homeostatic model assessment for insulin resistance (HOMA-IR) index were higher in young adults, with a considerable proportion of participants (22%) becoming insulin-resistant after pubertal development. In contrast, arterial hypertension was observed in 36% of prepubertal children compared with 18% of postpubertal young adults. Lipid values were within normal ranges without differences. Adiponectin and leptin remained at similar levels in adulthood, with a decrease in resistin. Conclusion Individuals with a history of EUGR have increased metabolic risk in adulthood, which emphasizes the importance of clinical follow-up from childhood to prevent the development of further future associated diseases.